2021
DOI: 10.3389/fnbeh.2021.685433
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Treatment for Social Defeat Stress

Abstract: Depression is a mood disorder characterized by disordered affect, thoughts, cognition, and behavior. Antidepressant therapy is often the primary treatment for depression. However, antidepressant therapy may cause unwanted side effects, and its effects are slow. Therefore, some patients are seeking alternative treatments for depression, such as acupuncture. However, there are many unclear points regarding the mechanism of the effect of acupuncture on depression. In recent years, we have reported that acupunctur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…As a complementary therapeutic treatment, acupuncture could improve symptoms in various neural diseases, such as depression, stroke rehabilitation, and Parkinson's disease [59][60][61]. Increasingly, clinical experiments have shown that the effectiveness of acupuncture is related to changes in brain activity.…”
Section: Discussionmentioning
confidence: 99%
“…As a complementary therapeutic treatment, acupuncture could improve symptoms in various neural diseases, such as depression, stroke rehabilitation, and Parkinson's disease [59][60][61]. Increasingly, clinical experiments have shown that the effectiveness of acupuncture is related to changes in brain activity.…”
Section: Discussionmentioning
confidence: 99%
“…EA effectively modulates NGF signaling, which not only affects sensory function but also has a neuroprotective value for sensory neurons [89] . Acupuncture stimulation suppressed NGF overexpression in the diseased state, indirectly demonstrating that EA inhibited hyperactivity in the sympathetic nervous system [90] . Therefore, we hypothesized that EA might inhibit NGF and sympathetic nerve sprouting, which would promote the analgesic effect of EA.…”
Section: Possible Mechanisms For the Regulation Of Sympathetic Nerves...mentioning
confidence: 99%
“…Dávila-Hernández et al's study showed that BDNF in the hippocampus was inversely associated with depression-like behavior and that the antidepressant effect of acupuncture might be related to improved hippocampal BDNF protein expression [ 61 ]. Moreover, acupuncture stimulation of Baihui (GV20) and Yingtang (Ex-HN3) restored reduced expression of BDNF in social defeat stress mice, which was not observed in antidepressants, suggesting that acupuncture can effectively correct the imbalance of BDNF expression compared with antidepressants [ 62 ]. In addition, many studies have explored the mechanism of acupuncture for treating depression.…”
Section: The Effect Of Bdnf In Acupuncture For Diabetes and Depressionmentioning
confidence: 99%